Resignification of contemporary aesthetics: An analysis of the profile of professionals in the field (Research, Society and Development, 2021)
The revolutions in the area of information technology and biotechnology made possible different forms of interaction, expression and creation of subjectivity. Both women and men start to live with great concern regarding personal care, beauty and aesthetics, seeking the perfect body and face. With this, the area of aesthetics has been increasingly recognized in the professional sphere, meeting the desires of most of the population in relation to beauty and well-being. Thus, the objective was to analyze, based on current legislation, the role and skills of professionals who can work in the esthetic area (physiotherapist, dermatologist and beautician) in contemporary times. To achieve the proposed objective, a documental research of the Curriculum Guidelines of the Physiotherapy and Medicine course with specialization in dermatology and aesthetics was carried out. There has been a huge growth in the area of aesthetics in recent years. Men and women became interested in the perfect and healthy body, with an increase in the demand for trained professionals in the area. What differentiates dermatofunctional physiotherapy, the dermatologist and the beautician is the study time and qualifications during undergraduate and graduate studies. The physiotherapist works in an integrated way with other professionals, helping in the treatment of certain pathologies of the integumentary system, while the beautician offers clients alternatives to improve their physical appearance, from skin cleaning to post-surgical care. The dermatologist is both a clinical and surgical specialty. It is concluded that dermatofunctional physiotherapy, the dermatologist and esthetics are professions with different responsibilities and competences, both in clear expansion of demand.